Вектори органзаційно-правового удосконалення практики функціонування національного природно-заповідного фонду - Римар, М. В.; Курницький, В. І. (Видавництво Львівської політехніки, 2014)
Висвітлено організаційні та правові параметри функціонування природно-заповідного фонду України. Зокрема проведено наукове обґрунтування застосування сучасних методик організації природно-заповідної справи з позиції лібералізації системи державного відомчого регулювання та спрощення природоохоронних механізмів у межах природно-заповідної сфери. Reveals the current state of objects of nature reserve fund of Ukraine, provision of maintenance of financial and economic resources to implement policies to protect the environment. Analyzed the system of economic instruments in implementing recreational activities. Deals with organizational and legal parameters of the Nature Reserve Fund of Ukraine. Specifically conducted scientific substantiation of application of modern methods of natural reserves in positions of public institutional liberalization and facilitation of environmental regulation mechanisms within natural protected areas. It is proved that even with substantial decentralization processes coordination plans recreational activities within protected areas fund to form a clear list of criteria to be taken into account when assessing and analyzing such plans. Formulated some aspects of the development and study of mechanisms of organizational and legal liberalization of the regulatory process to ensure adjustment and maintenance of recreational activities within the nature reserve fund of Ukraine. Argued for the need to adopt a more targeted tools and leverage the capacity to provide a regulatory effect and create real economic and financial platform for additional investments in nature conservation recreation.
Vectors orhanzatsiyno legal improvement practices of national nature reserve fund
Keywords: природно-заповідний фонд; природно-заповідний об’єкт; рекреа-ційна діяльність; природоохоронна діяльність; організаційне забезпечення; правове регулювання; natural areas; nature reserve facility; recreational activities; environmental activities; organizational support; legal regulation